2022
DOI: 10.3389/fbioe.2022.805996
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transient Expression of Plasmid DNA Using Poly (2-(N,N-Dimethylamino) Ethyl Methacrylate) in Plant Cells

Abstract: Nanomaterials have been widely studied for their potential to become the new generation of nanocarriers in gene transfection, yet it remains still difficult to apply them efficiently and succinctly to plant cells. Poly (2-(N,N-dimethylamino) ethyl methacrylate) (PDMAEMA), which possesses temperature and pH dual-sensitivity, has largely been applied in animal cells, but it is rarely involved in plant cells. As a proof of concept, PDMAEMA as a gene carrier is incubated with plasmid GFP (pGFP) to explore its tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
4
2
Order By: Relevance
“…Statistical significance analyses showed that incubation times between 15 and 60 min can be used with comparable efficiency. This finding differs from the Arabidopsis protoplast infection results, when a significantly longer incubation time was applied [21].…”
Section: Incubation Time With the Complex Determines The Efficiency O...contrasting
confidence: 96%
See 3 more Smart Citations
“…Statistical significance analyses showed that incubation times between 15 and 60 min can be used with comparable efficiency. This finding differs from the Arabidopsis protoplast infection results, when a significantly longer incubation time was applied [21].…”
Section: Incubation Time With the Complex Determines The Efficiency O...contrasting
confidence: 96%
“…Statistical significance analyses showed that incubation times between 15 and 60 min can be used with comparable efficiency. This finding differs from the Arabidopsis protoplast infection results, when a significantly longer incubation time was applied [21]. As shown in Figure 4A,B, the incubation of maize protoplasts with polyplexes composed of plasmid DNA (pGFP, [25]) vector containing the GFP gene and the cationic polymer generated a considerable number of green fluorescent cells.…”
Section: Incubation Time With the Complex Determines The Efficiency O...contrasting
confidence: 59%
See 2 more Smart Citations
“…Clarity Western Substrate (BIO-RAD) was used for chemiluminescent detection of the GFP protein. The detection was performed using a LI-COR Odyssey Infrared Imaging System (Tanon, 5,200, China) ( An et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%